A Study on The Job Replacement Impact of ChatGPT and Education Method - Dong Hwa Kim; Aktansi Kindiasari (International Journal of Artificial Intelligence Research, 2023)
This paper deals with the job impact of ChatGPT and education preparation for that, which will give an influence on many areas because it can be implemented with ease as just normal editing works and speak including code development by using huge data. Currently young generations will take a big impact on their job selection because ChatGPT can do well as much as human can do it in everywhere. Therefore, education method and system should be rearranged as new curriculums. However, government and officer do not understand well how it is serious in education. This paper provides education method and curriculum for AI education including ChatGPT through analyzing many papers and report, and experience